Investigation of the rheological properties of bitumen modified with different waste oils under various frequencies and temperatures - Yalcin, Erkut; Yilmaz, Mehmet (Pamukkale Univ, 2021)
In this study, the rheological properties of pure binders and modified bitumen that were prepared with these binders were investigated under various temperatures and frequencies. In the study, the B 50/70 class pure bitumen, which was obtained from the TUPRAS refinery in Batman, was used as the main binder. Waste oils were used as additives at 2%, 4%, 6%, 8%, 10%, 12% and 14% ratios. Pure and modified bitumen were subjected to dynamic shear rheometer (DSR) tests at 4 different temperatures (40 degrees C, 50 degrees C, 60 degrees C, and 70 degrees C) and 10 different frequencies (between 0.01 Hz and 10 Hz). As a result of the DSR tests, it was determined that the modified bitumen that was prepared with waste engine oil had higher complex shear modulus and lower phase angle values compared to the modified bitumen prepared with waste vegetable oil, which pointed to elastic behaviors at higher levels in favor of engine oil modification. It was also determined that waste vegetable oil proved more effective at 2% and 3% additive ratios in terms of the complex shear modulus values while waste engine oil modification was more effective at 2% and 4% additive ratios. In conclusion, it was discovered that waste engine oil was more effective in preparing modified bitumen compared to waste vegetable oil.
Keywords: Bitumen; Rheology; Waste engine oil; Waste vegetable oil; Mechanical analysis; Modification